Health care and Christian ethics - Gill, Robin (New studies in Christian ethics, 2006)
How can Christian ethics make a significant contribution to health care ethics in today's Western, pluralistic society? Robin Gill examines the 'moral gaps' in secular accounts of health care ethics and the tensions within specifically theological accounts. He explores the healing stories in the Synoptic Gospels, identifying four core virtues present within them - compassion, care, faith and humility - that might bring greater depth to a purely secular interpretation of health care ethics. Each of these virtues is examined in turn, using a range of topical issues including health care rationing, genetics, HIV/AIDS, withholding/withdrawing nutrition from PVS patients, and the empirical evidence which suggests a connection between religion and health. Professor Gill also argues that these four virtues are shared by other major religious and humanistic traditions and that, together with secular principles, they can enrich health care ethics even in a pluralistic society.